Cancer Prevention in Patients with GERD and Barrett's Esophagus—Medicine. Issue 1 (March 2021) - Scarpignato, Carmelo; Wang, David H.
Gastro-esophageal reflux disease (GERD) and Barrett's esophagus are risk factors for esophageal adenocarcinoma (EAC). Chemoprevention is an attractive strategy, more effective than identifying early disease. Since acid reflux can lead to increased cell proliferation, decreased apoptosis, production of reactive oxygen species, DNA damage, and esophageal production of proinflammatory and pro-proliferative cytokines, proton pump inhibitors (PPIs) alone, or in combination with COX-inhibition, are the most suitable chemopreventive agents. Other compounds (statins, metformin, and selected nutraceuticals) cannot currently be recommended. Data are strong enough to warrant PPI treatment of virtually all patients with Barrett's esophagus, although the best regimen has not yet been defined.